A comprehensive environmentally friendly ground source heat pump backfill material and preparation method
By adding powdered activated carbon to the ground source heat pump backfill material, the adsorption and thermal conductivity of the material are improved, the hidden dangers of existing materials to the underground environment are solved, and more efficient heat pump system operation and environmental protection effects are achieved.
Patent Information
- Application Number
- CN202310288734.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-23
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-03-23
AI Technical Summary
On the basis of ensuring thermal conductivity, existing ground source heat pump backfill materials lack effective adsorption and environmental protection performance, which may lead to underground environmental pollution, affecting the formation balance and purification of aquifers.
A comprehensive environmentally friendly ground source heat pump backfill material consisting of silicate cement, quartz sand, water, bentonite and powdered activated carbon is used to improve the adsorption and thermal conductivity of the material by adjusting the weight ratio of each component and adding activated carbon.
It improves the adsorption performance of backfill materials, significantly improves the removal rate of methylene blue and hexavalent chromium, enhances the environmental protection performance of the material, improves the thermal conductivity, and reduces the initial investment and operating costs of system operation.
Smart Images

Figure CN116409969B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a comprehensive environmentally friendly ground source heat pump backfill material and a preparation method thereof. Background Art
[0002] Ground source heat pumps are highly efficient and energy-saving devices that use a small amount of high-quality electricity to extract low-grade geothermal energy for use in buildings. They can reduce carbon emissions while meeting the cooling and heating needs of buildings. They have received extensive attention and application in recent years due to their energy-saving, high-efficiency, and environmentally friendly characteristics. Ground source heat pumps are classified into different types according to the form of heat source, and the most common application form is the buried pipe ground source heat pump system. Grouting materials are needed to backfill between the buried pipe and the soil. The properties of these materials have a certain impact on the heat transfer effect of the system and the underground environment around the buried pipe.
[0003] Backfill material is the material used to fill the gap between the borehole wall and the buried pipe in the ground heat exchange system. The thermal conductivity, mechanical properties and mechanical properties of the backfill material have a crucial impact on the operating efficiency of the heat pump system and the surrounding underground environment. When the ground heat exchange system is improperly installed and unsupervised in a contaminated site, it may cause contaminants to migrate from the surface to the aquifer. When there is a potential leak of refrigerant or antifreeze-based carrier fluid underground, it is difficult for people to find it. The ground source heat pump unit and heat exchange equipment are in contact with the soil and groundwater for a long time during operation. The geological structure of the stratum is complex, the groundwater is highly concealed, and it flows slowly in the stratum. Once there is pollution or its original balance is broken, it is not only difficult to detect, but also requires a long repair period.
[0004] During the drilling process, due to the possibility of destroying the balance of the formation, if the aquiclude is destroyed by external forces and becomes a weak permeable layer, it may cause the water in the shallow underground polluted aquifer to migrate and infiltrate into the deep unpolluted aquifer, and even cause greater pollution and spread. If water pollution remains in the aquifer for a long time without being discovered by humans, it will cause irreparable and serious harm to the underground environment.
[0005] At present, the technical solutions for existing backfill materials are mostly focused on improving their thermal conductivity or economic benefits, while there are few studies on the material's adsorption performance of pollutants in the underground environment itself, and the underground environmental pollution that may be generated during the backfill process. Due to the complexity and diversity of the underground environment, in addition to having good heat exchange performance, backfill materials also need to have environmentally friendly properties to avoid pollution of the underground environment, especially groundwater. With the country's vigorous promotion of energy conservation and emission reduction, and the urgent need to build a resource-saving and environmentally friendly society, more and more buildings will adopt ground source heat pump systems. Therefore, the study of the comprehensive environmental performance of buried pipe backfill materials is of great practical significance for improving the operating efficiency of heat pump systems and protecting the underground environment.
[0006] In summary, how to provide a comprehensive environmentally friendly ground source heat pump backfill material with adsorption performance while ensuring the original thermal conductivity of the backfill material is a problem that the present invention needs to solve. Summary of the invention
[0007] The technical problem to be solved by the present invention is to make up for the deficiencies of the prior art and provide a comprehensive environmentally friendly ground source heat pump backfill material.
[0008] To solve the above technical problems, the technical solution of the present invention is:
[0009] A comprehensive environmentally friendly ground source heat pump backfill material, which is composed of a basic component and an admixture, wherein the basic component is composed of silicate cement, quartz sand, water and bentonite, and the admixture is powdered activated carbon;
[0010] The weight ratio of Portland cement, quartz sand, water, bentonite and powdered activated carbon is:
[0011] Portland cement: 1.0 part;
[0012] Quartz sand: 1.75-2.25 parts;
[0013] Water: 0.75-1.05 parts;
[0014] Bentonite: 0.07-0.17 parts;
[0015] Powdered activated carbon 0.01-0.05 parts.
[0016] Furthermore, the weight ratio of silicate cement, quartz sand, water, bentonite and powdered activated carbon is:
[0017] Portland cement: 1.0 part;
[0018] Quartz sand: 2.0 parts;
[0019] Water: 0.95 parts;
[0020] Bentonite: 0.16 parts;
[0021] Powdered activated carbon 0.03-0.05 parts.
[0022] Furthermore, the weight ratio of silicate cement, quartz sand, water, bentonite and powdered activated carbon is:
[0023] Portland cement: 1.0 part;
[0024] Quartz sand: 2.0 parts;
[0025] Water: 0.95 parts;
[0026] Bentonite: 0.16 parts;
[0027] 0.05 parts of powdered activated carbon.
[0028] Furthermore, the powdered activated carbon is powdered wood activated carbon or powdered coal activated carbon.
[0029] Furthermore, the powdered wood activated carbon has a pH value of 2.6, a particle size of 200 mesh, and a specific surface area of 1056 m 2 / g, iodine value is 1077 mg / g, moisture is 4.9%; the pH value of the powdered coal-based activated carbon is 7.6, the particle size is 200 mesh, and the specific surface area is 1089 m 2 / g, iodine value is 1075 mg / g, and moisture content is 5.5%.
[0030] Furthermore, the strength grade of the silicate cement is ≥42.5.
[0031] Furthermore, the particle size of the quartz sand is 40-70 mesh and the bulk density is 1.87 g / cm 3 .
[0032] Furthermore, the bentonite is sodium bentonite with a particle size of 200 mesh and a bulk density of 1.6 g / cm 3 .
[0033] A method for preparing the above-mentioned comprehensive environmentally friendly ground source heat pump backfill material comprises the following steps:
[0034] S1: preparing the raw materials of each component according to the weight ratio; cleaning the mixing pot of the cement mortar mixer and drying the mixing pot;
[0035] S2: Add the other raw materials except water into a stirring pot, stir and mix well to obtain a dry material mixture;
[0036] S3: Add water to the dry material mixture and stir until the slurry is uniform to obtain the comprehensive environmentally friendly ground source heat pump backfill material.
[0037] Further, in step S2, the cement mortar mixer is set to operate at a low speed, that is, the rotation speed is 140±5r / min, the revolution speed is 62±5r / min, and the mixing time is 120s;
[0038] In step S3, the water is divided into two equal parts, one equal part of water is first added to the dry material mixture, and the cement mortar mixer continues to run at a low speed for 240 seconds; then the cement mortar mixer is stopped, and the material on the inner wall of the mixing pot is scraped into the mixing pot with a scraper; another equal part of water is added, and the cement mortar mixer is set to run at a high speed, that is, rotation at 285±10r / min, revolution at 125±10r / min, and the mixing time is 180s.
[0039] The beneficial effects that can be achieved by the present invention are:
[0040] (1) The proportion of traditional cement-based materials was deconstructed and reorganized, and the content of bentonite in the basic components was greatly increased. Compared with traditional raw slurry backfill materials, it has better fluidity and lower permeability, and also has a certain adsorption effect on pollutants.
[0041] (2) The addition of activated carbon can make the backfill material have adsorption properties, effectively improving the environmental performance of the backfill material. Compared with the material without activated carbon, the adsorption of methylene blue (organic pollutant) can be increased by 67.9%, and the removal rate of hexavalent chromium, a heavy metal pollutant in groundwater, can be increased from less than 10% to more than 70%. This is because activated carbon is a porous structure material obtained by high-temperature carbonization of materials such as wood, coal, and fruit shells. Its pores can account for 70% to 80% of its total volume. The developed microporous structure brings a huge specific surface area to this type of material, thus giving it a strong adsorption capacity.
[0042] (3) The addition of activated carbon can also make the backfill material have better thermal conductivity, with a thermal conductivity coefficient of up to 2.67 W / m·K, which can improve the heat exchange efficiency. The required buried pipe length can be reduced by up to about 20% compared with the buried pipe length of the original slurry backfill material, effectively reducing the initial investment and operating costs of the system operation, with significant economic benefits. This is because activated carbon has good intermolecular forces, which can better condense silicate cement, quartz sand and bentonite together during the solidification process of the material. There are basically no pores on the surface of the solidified material. Therefore, activated carbon can increase the density of the material to make the thermal conductivity of the material itself better. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a graph showing the change in material fluidity at different bentonite addition amounts.
[0044] Figure 2 This is a graph showing the change in material fluidity under different ratios.
[0045] Figure 3 This is a graph showing the change in thermal conductivity of materials at different bentonite addition amounts.
[0046] Figure 4 This is the state diagram of the specimen under different bentonite addition amounts.
[0047] Figure 5 This is a graph of thermal conductivity of materials under different ratios.
[0048] Figure 6 This is a graph showing the volume change of materials at different bentonite addition amounts when the material age is 28 days.
[0049] Figure 7 This is a graph showing the volume of material with a sand-to-cement ratio of 2 as a function of age.
[0050] Figure 8 This is a graph showing the volume of material with a water-cement ratio of 0.85 as a function of age.
[0051] Fig. 9 This is a graph showing the change in compressive strength of materials with different amounts of bentonite added.
[0052] Fig.10 This is a graph of the compressive strength of materials under different ratios.
[0053] Fig.11 This is a material fluidity diagram with different activated carbon addition amounts.
[0054] Fig.12 This is a graph showing the change in material fluidity with different graphite additions.
[0055] Fig.13 This is a graph showing the effect of different activated carbon additions on the thermal conductivity of the material.
[0056] Fig.14 This is a graph of thermal conductivity of materials with different graphite additions.
[0057] Fig.15 This is a graph of the methylene blue standard curve.
[0058] Fig.16 1 and 2 are the relationship between the amount of material added and the removal rate of methylene blue.
[0059] Fig.17 1 is a graph showing the relationship between the amount of material added and the removal rate of methylene blue in Example 1 and Example 2.
[0060] Fig.18 It is the standard curve of hexavalent chromium.
[0061] Fig.19 This is a graph showing the relationship between the amount of material added and the amount of Cr adsorbed and removed in Comparative Example 1.
[0062] Fig. 20 This is a graph showing the relationship between the amount of material added and the amount of Cr adsorbed and removed in Example 1.
[0063] Fig.21 This is a graph showing the relationship between the amount of material added and the amount of Cr adsorbed and removed in Comparative Example 2.
[0064] Fig. 22 This is a graph showing the relationship between the amount of material added and the amount of Cr adsorbed and removed in Example 2. DETAILED DESCRIPTION
[0065] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0066] The materials and equipment used in the following examples and comparative examples are explained as follows:
[0067] Portland cement: ordinary Portland cement, the strength grade of Portland cement is ≥42.5.
[0068] Quartz sand: particle size is 40-70 mesh, bulk density is 1.87 g / cm 3 .
[0069] Bentonite: Sodium bentonite, particle size 200 mesh, bulk density 1.6 g / cm 3 .
[0070] Powdered wood activated carbon: pH value is 2.6, particle size is 200 mesh, specific surface area is 1056 m 2 / g, iodine value is 1077mg / g, and moisture content is 4.9%.
[0071] Powdered coal-based activated carbon: pH value is 7.6, particle size is 200 mesh, specific surface area is 1089 m 2 / g, iodine value is 1075mg / g, and moisture content is 5.5%.
[0072] Graphite: Natural flake graphite, particle size 80 mesh, carbon content 99.5%, grayness 0.35%, moisture 0.15%.
[0073] Cement mortar mixer: JJ-5 cement mortar mixer, including low speed gear (rotation 140±5r / min, revolution 62±5r / min) and high speed gear (rotation 285±10r / min, revolution 125±10r / min).
[0074] The concepts mentioned below are explained as follows:
[0075] Water-cement ratio (W / C): refers to the mass ratio of water to silicate cement.
[0076] Sand-cement ratio (S / C): refers to the mass ratio of quartz sand to Portland cement.
[0077] In the following embodiments and comparative examples, the preparation method of the comprehensive environmentally friendly ground source heat pump backfill material is as follows:
[0078] S1: Prepare the raw materials of each component according to the weight ratio; clean the mixing pot of the cement mortar mixer and dry the mixing pot.
[0079] S2: Add the other raw materials except water into the mixing pot in any order; set the cement mortar mixer to run at a low speed (rotation 140±5r / min, revolution 62±5r / min) for 120s, and mix thoroughly to obtain a dry material mixture.
[0080] S3: In step S3, the water is divided into two equal parts, one equal part of water is added to the dry material mixture first, and the cement mortar mixer continues to run at a low speed for 240 seconds; then the cement mortar mixer is stopped, and the material on the inner wall of the mixing pot is scraped into the mixing pot with a scraper; another equal part of water is added, and the cement mortar mixer is set to run at a high speed, i.e., rotation at 285±10r / min, revolution at 125±10r / min, and the mixing time is 180 seconds. The slurry is evenly stirred to obtain a comprehensive environmentally friendly ground source heat pump backfill material.
[0081] In the following embodiments and comparative examples, the performance test preparation precautions of the comprehensive environmentally friendly ground source heat pump backfill material are as follows:
[0082] (1) After preparing the slurry of the comprehensive environmentally friendly ground source heat pump backfill material according to the above preparation method, set aside a portion of the slurry for fluidity testing, and use the mold for injection molding of the remaining material. Before injection molding, it is necessary to apply a thin layer of engine oil on the inner surface of the mold and block the demoulding holes. Slowly load the evenly mixed mortar into the mold, then use a scraper to tamp along the inner wall of the mold, and finally scrape the slurry above the upper edge of the mold. Fix the mold after injection molding on the vibration table and vibrate it 30 times, remove the bubbles in the slurry and then remove it.
[0083] (2) The molded material was placed in a curing box at a temperature of 20±3°C and a relative humidity of 95% for curing. After standing for 24 hours, the molded test pieces were taken out for demolding and numbering. Considering that the various properties of the material in the saturated state will be tested in subsequent experiments, the test pieces were immersed in a saturated calcium hydroxide solution at 17~23°C for curing.
[0084] (3) Take the material out of the curing solution and use absorbent paper to absorb the surface moisture to prevent the surface moisture from affecting the test results. The present invention defines the state of the material at this time as the saturated state of the material. Since the backfill material is a porous medium, in order to avoid the influence of moisture content on thermal conductivity, the thermal conductivity coefficient in the saturated state is uniformly measured. Volume shrinkage and compressive strength of the material to be tested.
[0085] (4) After completing the above tests, the specimen is completely dried and then ground into powder using a mortar. The ground powder needs to be washed with distilled water and dried again. Finally, the powder is sieved using a vibrating sieve machine to select the appropriate particle size range for testing the material's adsorption performance for the organic pollutant methylene blue and the inorganic pollutant hexavalent chromium.
[0086] In the following embodiments and comparative examples, the performance test method of the comprehensive environmentally friendly ground source heat pump backfill material is as follows:
[0087] (1) Fluidity test method:
[0088] The backfill material used in the present invention is studied based on cement mortar, so the fluidity is determined by referring to the method recommended in "Method for Determining Fluidity of Cement Mortar" (GB / T2419-2005). The fluidity of the present invention is tested using the NLD-3 cement mortar fluidity tester. The fluidity test of the slurry must be completed within 6 minutes after the slurry is prepared, and if the instrument has not been used for 24 hours, it is necessary to perform 25 empty jumps for adjustment before the test.
[0089] 1) After cleaning the equipment, inject the prepared slurry into the mold twice. The first time, add it to two-thirds of the mold height, then use a scraper to scratch it 5 times in two perpendicular directions, and then use a tamping rod to hammer it 15 times from the edge to the center; after the second slurry is injected to 20 mm above the lower mold section, repeat the previous steps, but the number of hammering is reduced to 10 times, and then use a scraper to scrape off the excess slurry at an angle to make it level with the mold. During the scraping process, you need to hold the test mold steady by hand to prevent it from moving.
[0090] 2) After slowly lifting the mold, start the instrument immediately, vibrate once per second, and stop the instrument for measurement after 25 beats in one cycle.
[0091] 3) Use a vernier caliper to measure the longest diameter and the average of the perpendicular diameter as the fluidity measured at that time. Repeat each set of experiments three times and take the average value as the final fluidity of the component. Clean the experimental instruments used in the process between each set of measurements.
[0092] (2) Thermal conductivity test method:
[0093] The present invention adopts a Hot Disk thermal constant analyzer to test the thermal properties of the material, and uses a polyimide coated probe that can test solids at room temperature. Before the test begins, the material is taken out of the curing solution. To prevent surface moisture from affecting the test results, absorbent paper is used to absorb the surface moisture. The present invention defines the state of the material at this time as the saturated state of the material. Because the backfill material is a porous medium, in order to avoid the influence of moisture content on thermal conductivity, the thermal conductivity coefficient in the saturated state is uniformly measured. The specific steps are as follows:
[0094] 1) Before the test begins, clamp the probe between two specimens, place the sample on a tray, and squeeze it using screws and gaskets to make both sides of the probe contact as closely as possible with the surface to be tested to reduce contact thermal resistance.
[0095] 2) After preheating the instrument for a period of time, set the size of the sample to be tested, test time and test power before starting the measurement.
[0096] (3) Volume shrinkage test method:
[0097] The volume shrinkage rate determination of the present invention refers to the "Test Method for Basic Properties of Building Mortar" (JGJ / T70-2009). The experimental instrument used in the experiment is a BC-176 vertical mortar shrinkage instrument, which consists of an indicator (range of ±5 mm), a standard rod (length of 176±0.02 mm) and a lower platform.
[0098] 1) When prefabricating the specimen, it is necessary to install shrinkage probes on both ends of the specimen during mold making. During the hardening and shrinkage process of cement mortar, the vertical shrinkage meter obtains the volume change of the test block by comparing the length difference between the standard rod and the specimen at different times.
[0099] 2) Three test molds need to be made for comparison under the same ratio. After confirming that the error of the three sets of data is less than 15%, the arithmetic mean is taken as the experimental result. If the error is too large, the experiment needs to be repeated.
[0100] (4) Compressive strength test method:
[0101] The present invention adopts a YAW-300E constant stress compression and flexural testing machine for determination, and the experimental method refers to the method recommended in "Basic Performance Test Method of Building Mortar" (JGJ / T70-2009).
[0102] 1) During the experiment, the center of the specimen needs to be aligned with the center of the bottom plate of the testing machine and the pressure-bearing surface needs to be perpendicular to the top surface. Then, the machine needs to be adjusted to continuously and evenly add load to the specimen. When the specimen is damaged, the machine automatically stops adding load and records the material damage load.
[0103] 2) Repeat the above steps three times, take the arithmetic mean of the data and define the data as the ultimate compressive strength of the experiment. If the error between the upper and lower extreme values and the middle value is more than 15%, the experiment needs to be repeated.
[0104] (5) Adsorption performance test method:
[0105] The present invention conducts an adsorption isotherm experiment, i.e., a static adsorption experiment, on the backfill material. The adsorption isotherm curve is a method for characterizing the adsorption properties of a material in adsorption thermodynamics. The method analyzes the curve of the concentration relationship between the adsorbent and the adsorbate molecules at the two-phase interface when the adsorption process reaches equilibrium by fixing the temperature, and uses the adsorption equation to represent the curve law. The adsorption capacity and adsorption strength of the material for pollutants can be determined according to the parameters of the adsorption equation.
[0106] 1) In the experiment, after determining the type of material, weigh samples of different masses and put them into 150 ml conical flasks respectively, and add 50 ml of methylene blue solution with an initial concentration of 10 mg / L and Cr solution with an initial concentration of 20 mg / L into the conical flasks, and conduct experiments on organic pollutants and inorganic pollutants respectively.
[0107] 2) Use an air bath thermostat oscillator, set the constant temperature at 25 °C and the constant speed at 160 r / min to oscillate the sample for 12 h.
[0108] 3) After the shaking is completed, let it stand for a while, then filter the supernatant using a filter membrane, and measure the absorbance of the supernatant at 664 nm using a spectrophotometer.
[0109] Example 1
[0110] A comprehensive environmentally friendly ground source heat pump backfill material consists of silicate cement, quartz sand, water, bentonite and coal-based activated carbon, with the weight ratio of each component being 1:2:0.95:0.16:0.03.
[0111] Example 2
[0112] A comprehensive environmentally friendly ground source heat pump backfill material consists of silicate cement, quartz sand, water, bentonite and coal-based activated carbon, with the weight ratio of each component being 1:2:0.95:0.16:0.05.
[0113] Comparative Example 1
[0114] A comprehensive environmentally friendly ground source heat pump backfill material consists of silicate cement, quartz sand, water, bentonite and wood activated carbon, with the weight ratio of each component being 1:2:0.95:0.16:0.03.
[0115] Comparative Example 2
[0116] A comprehensive environmentally friendly ground source heat pump backfill material consists of silicate cement, quartz sand, water, bentonite and wood activated carbon, with the weight ratio of each component being 1:2:0.95:0.16:0.05.
[0117] Comparative Example 3
[0118] A ground source heat pump backfill material consists of silicate cement, quartz sand, water and bentonite, with the weight ratio of each component being 1:2:0.95:0.16.
[0119] Comparative Example 4
[0120] A ground source heat pump backfill material consists of silicate cement, quartz sand, water, bentonite and graphite, with the weight ratio of each component being 1:2:0.95:0.16:0.06.
[0121] Comparative Example 5
[0122] A ground source heat pump backfill material consists of silicate cement, quartz sand, water, bentonite and graphite, with the weight ratio of each component being 1:2:0.95:0.16:0.1.
[0123] The above embodiments and comparative examples are explained and analyzed as follows:
[0124] Reasons for determining the weight ratio of Portland cement, quartz sand, water and bentonite to be 1:2:0.95:0.16 in the basic components:
[0125] Firstly, the water-cement ratio and sand-cement ratio were explored. The water-cement ratio was selected in the range of 0.65-1.05 (interval 0.1), and the sand-cement ratio was selected in the range of 1.5-2.5 (interval 0.25). The performance of 25 groups of materials obtained by matching different proportions one by one were tested, and the optimal proportion of cement, water and sand as the basic components was determined to be: water-cement ratio of 0.95, sand-cement ratio of 2.
[0126] Then, under the ratio of water-cement ratio of 0.95 and sand-cement ratio of 2, the amount of bentonite added was explored. After adjusting the amount of bentonite added to 0, 2.5%, 5% and 7.5% of the total solid mass fraction, comparative experiments were carried out to analyze the influence of bentonite on material properties when it was used as a basic component.
[0127] Combined with engineering specifications and relevant research conclusions, when bentonite is selected to account for 5% of the total solid mass fraction (equivalent to a weight ratio of bentonite to Portland cement of 0.16:1), the change patterns of various material properties with the water-cement ratio and sand-cement ratio and the selection range under different proportions are analyzed.
[0128] (1) Experimental plan for flow properties of basic components:
[0129] 1) Analysis of material fluidity under different bentonite additions
[0130] like Figure 1 The figure shows the effect of different amounts of bentonite on the fluidity of the material. It can be seen that the fluidity of the material without bentonite is too high, reaching 34 cm without shaking, but the fluidity will decrease as the proportion of bentonite added increases. This is because the strong water absorption of bentonite will indirectly affect the water consumption of the material, so if you want to have good fluidity, you need to increase the water-cement ratio. However, when the water-cement ratio is increased to a certain extent, the reaction ability of the material with water reaches saturation. Although continuing to increase the amount of water will increase the fluidity of the slurry, it will also cause the slurry to bleed, which is not conducive to the performance of the material after hardening. Combined with relevant specifications and engineering experience, 5% of the solid material is selected as the amount of bentonite added.
[0131] 2) Analysis of material fluidity under different ratios
[0132] The change trend of the fluidity of the backfill material after the addition of 5% bentonite is as follows Figure 2As shown. The fluidity increases with the increase of water-cement ratio (W / C) and decreases with the increase of sand-cement ratio (S / C). The worst fluidity of the material is 14.25 cm when the water-cement ratio is 0.65 and the sand-cement ratio is 2.5; the best fluidity is 27.2 cm when the water-cement ratio is 1.05 and the sand-cement ratio is 1.5.
[0133] By fixing the sand-cement ratio and analyzing the effect of the water-cement ratio on fluidity, it can be found that at the same sand-cement ratio, the fluidity will increase as the water-cement ratio increases. At different sand-cement ratios, the degree of improvement in fluidity of the slurry with a water-cement ratio of 1.05 is different from that of the slurry with a water-cement ratio of 0.65, indicating that fluidity is affected by both the water-cement ratio and the sand-cement ratio.
[0134] By fixing the water-cement ratio and analyzing the effect of the sand-cement ratio on fluidity, it can be found that at the same water-cement ratio, the fluidity decreases with the increase of the sand-cement ratio.
[0135] The above phenomenon shows that the main factor affecting the fluidity of the material is the water content of the material. However, when the sand in the material increases, the internal friction of the slurry will increase because the sand surface is relatively rough, thereby reducing the fluidity. When the water-cement ratio is lower than 0.85, the change in slurry fluidity is more affected by the sand-cement ratio. There is a clear downward trend before the sand-cement ratio rises to 2. When the water-cement ratio is higher than 0.85 and the sand-cement ratio is greater than 2.25, it will have a significant impact on the fluidity of the material.
[0136] (2) Experimental plan for thermal conductivity of basic components:
[0137] 1) Analysis of thermal conductivity of materials under different bentonite additions
[0138] like Figure 3 The figure shows the change of thermal conductivity with different bentonite additions. It can be seen that the thermal conductivity of the material without bentonite in the saturated state is the best. With the increase of bentonite, the thermal conductivity will decrease to a certain extent. There will be a large change in the addition range of 2.5% to 5%. The thermal conductivity of 7.5% bentonite is reduced by 0.274 W / (m·K) compared with no addition. This is because the addition of bentonite will increase the water content per unit volume, reduce fluidity and increase porosity, which will cause the thermal conductivity to decrease.
[0139] like Figure 4As shown in the figure, the bentonite addition of the specimens from left to right is 0, 2.5%, 5% and 7.5% respectively. It can be seen that there is a large piece of yellow sand at the bottom of the material without bentonite, and there is an accumulation of aggregate. In actual application, the material without bentonite will have a high local thermal conductivity but non-isotropic, which is not conducive to the overall heat exchange of the borehole. Adding an appropriate amount of bentonite can improve this phenomenon. When the bentonite addition is 5%, the thermal conductivity of the material is 1.7 W / (m·K), and the fluidity is good, so bentonite with 5% solid material is selected as the basic component.
[0140] 2) Analysis of thermal conductivity of materials under different ratios
[0141] Depend on Figure 5 It can be seen that when the water-cement ratio is 0.85, 0.95 and 1.05 after the bentonite addition is fixed, the thermal conductivity of the material is positively correlated with the sand-cement ratio, and the highest thermal conductivity appears at the water-cement ratio of 0.85 and the sand-cement ratio of 2.5, which is 1.982 W / (m·K). This is because the thermal conductivity of sand is relatively high. As the volume fraction of sand per unit volume increases, the thermal conductivity of the material is improved. When the water-cement ratio is 0.85 and 0.95, the thermal conductivity is significantly improved in the sand-cement ratio range of 1.75 to 2, while the overall improvement is relatively limited when the water-cement ratio is 1.05. This is because the water-cement ratio is too high, resulting in a decrease in the influence of the sand-cement ratio on the thermal conductivity of the material.
[0142] When the water-cement ratio is 0.65 and 0.75, the change in thermal conductivity has a similar trend to other water-cement ratios when the sand-cement ratio is low, but the thermal conductivity decreases with the increase of the sand-cement ratio. Figure 2 ) for analysis, when the fluidity is too low, the thermal conductivity of the material will be significantly reduced, which indirectly verifies that the thermal conductivity of the material is affected by the flow properties. When the fluidity is too low, the porosity will be higher than other materials during the material molding process, resulting in more water in the material instead of solid components, thereby reducing the thermal conductivity of the material.
[0143] When the sand-cement ratio is less than 2, it can be seen that the thermal conductivity of the material is negatively correlated with the water-cement ratio, while when the sand-cement ratio is greater than 2, the remaining three groups of water-cement ratios still have the same trend. Combining the effects of water-cement ratio and sand-cement ratio on thermal conductivity, it is found that the amount of water added during material mixing is one of the main factors affecting thermal conductivity. Combining the comprehensive effects of fluidity and thermal conductivity, the material with a water-cement ratio of 0.85 and a sand-cement ratio of 2.25 is currently the best ratio.
[0144] (3) Experimental plan for volume stability of basic components:
[0145] 1) Analysis of material volume stability under different bentonite additions
[0146] like Figure 6As shown in the figure, the volume stability of the backfill material will be increased after the addition of bentonite. This is because bentonite, as a material with good water absorption, can delay water loss, make the humidity inside the cement-based backfill material evenly distributed, and can keep a high humidity inside the material for a long time, slowing down the change of capillary tension caused by water evaporation, thereby increasing the volume stability of the material.
[0147] 2) Analysis of material volume stability under different ratios
[0148] Figure 7 The volume shrinkage of the material at different water-cement ratios when the sand-cement ratio is fixed at 2; Figure 8 The volume shrinkage of the material under different sand-cement ratios when the water-cement ratio is fixed at 0.85. The changes in the volume of the material at different ages are different. The volume changes of the material at 7 to 14 days are more drastic. Although it will shrink after 14 days, the overall changes tend to be stable.
[0149] Depend on Figure 7 It can be seen that the lower the water-cement ratio of the material at the same age, the smaller the volume change. Therefore, the volume change of the material is affected by the water-cement ratio mainly because: in the early and middle stages, the free water content of the material is abundant, and the volume shrinkage caused by the loss of water due to evaporation is small. With the change of age, the internal pores of the material will also decrease as the water-cement ratio decreases. At this time, the volume shrinkage caused by water evaporation will be more obvious, so the volume change of the material with a small water-cement ratio is small.
[0150] like Figure 8 As shown in the figure, the volume shrinkage caused by the sand-to-cement ratio has similar reasons. A high sand ratio will make the material denser. When the content of cementitious material decreases, the capillary pores will decrease and the slurry will lose water seriously. Therefore, the higher the sand-to-cement ratio, the greater the volume change of the material.
[0151] According to the material volume shrinkage test results, the material with a water-cement ratio of 0.85 and a sand-cement ratio of 2.25 has a higher volume shrinkage in 28 days than the material with a water-cement ratio of 0.85 and a sand-cement ratio of 2. In engineering applications, in order to ensure that the thermal conductivity meets the requirements while pursuing higher fluidity and lower volume shrinkage materials, a water-cement ratio of 0.85 and a sand-cement ratio of 2 should be selected.
[0152] (4) Basic component compressive strength test plan:
[0153] 1) Analysis of material compressive strength under different bentonite additions
[0154] like Fig. 9The figure shows the compressive strength of the material under different bentonite additions. It can be seen that the compressive strength of the material with bentonite added is higher than that of the material without bentonite, and the compressive strength decreases with the increase of bentonite addition. The reason is that the material strength decreases due to the high water-cement ratio. The addition of bentonite can absorb some water and thus enhance the compressive performance of the material. However, as the amount of bentonite added increases, the bonding ability between the bentonite itself and the aggregate is not high and will cause the fluidity of the slurry to decrease. Therefore, as the amount of bentonite added increases, the mechanical properties of the material will be reduced to a certain extent.
[0155] 2) Analysis of compressive strength of materials under different ratios
[0156] Depend on Fig.10 It can be seen that under different water-cement ratios, the compressive strength of the material increases with the increase of the sand-cement ratio. At the same time, the compressive strength of the material is inversely proportional to the water-cement ratio. When the sand-cement ratio is high, the compressive strength of the material is more obviously affected by the water-cement ratio. When the sand-cement ratio is fixed at 2.5, it can be found that the compressive strength of the material at a water-cement ratio of 1.05 is 49.2% lower than that at a water-cement ratio of 0.65, indicating that the proportion of cement components in the hydration process of the material will affect the mechanical properties of the material after hardening. Similarly, the compressive strength is compared when the water-cement ratio is 0.65 and the sand-cement ratio is 2.5. When the sand-cement ratio is 1.5, the compressive strength of the material increases by 41.5%.
[0157] According to the above experimental results, considering the effects of different ratios on material fluidity, thermal conductivity, volume stability and compressive strength, a water-cement ratio of 0.85, a sand-cement ratio of 2, and a 5% bentonite ratio were selected as the basic components of the backfill material.
[0158] In addition, the effect of admixtures on the ratio of basic components must also be considered. Graphite is very stable and is often used to improve the thermal conductivity of backfill materials. Activated carbon also has stable chemical properties and good adsorption properties, which can improve the environmental friendliness of the material. However, according to relevant literature, the addition of graphite and activated carbon will reduce the fluidity of the material. In order to prevent the performance of the material with the addition of admixtures from being affected by fluidity, the water-cement ratio is increased to 0.95, and the sand-cement ratio remains unchanged.
[0159] Therefore, in the basic components, the weight ratio of silicate cement, quartz sand, water and bentonite is determined to be 1:2:0.95:0.16.
[0160] The reasons for the selection of the type and specific gravity of admixtures are explained as follows:
[0161] Graphite was added as an admixture at 2% to 10% (interval 2%) of the cement mass, and activated carbon was added at 1% to 5% (interval 1%) of the cement mass to further modify the material. The effects of the addition of activated carbon and graphite on the material properties were analyzed, and the optimal addition amounts of these two materials when used as additives were studied.
[0162] (1) Experimental scheme of the effect of graphite and activated carbon on material fluidity of the present invention:
[0163] 1) Analysis of the influence of activated carbon on material fluidity
[0164] like Fig.11 As shown in the figure, the fluidity of the slurry decreases with the increase of activated carbon. This is because activated carbon has a developed microporous structure and a very large specific surface area. Although it is hydrophobic, its strong adsorption will cause it to adsorb on the surface of gravel or combine with bentonite particles with good adsorption, thereby reducing the fluidity of the slurry. As the amount of activated carbon increases, the change in fluidity decreases linearly, and the effect of coal-based activated carbon on fluidity is greater than that of wood-based activated carbon.
[0165] 2) Analysis of the influence of graphite on material fluidity
[0166] like Fig.12 The figure shows the change in material fluidity after adding different masses of graphite. It can be seen that the addition of graphite will reduce the material's fluidity, which is about 21% lower than when not added at the maximum amount. Among them, there are more drastic changes when the amount is 4% to 6%, and the changes in the rest of the range are relatively stable. This is because graphite, as a hydrophobic material, cannot reduce fluidity by absorbing water, but natural flake graphite is not easily wetted in water, and its particles will agglomerate under the action of hydrophobic force. The agglomerated graphite will float on the surface of the slurry due to its low density, and the graphite microclusters will increase the viscosity of the slurry surface, thereby affecting the material's fluidity.
[0167] (2) Experimental scheme for the effect of graphite and activated carbon on thermal conductivity of materials:
[0168] This experiment uses the above-mentioned backfill material preparation method and performance test steps. Graphite is a high thermal conductivity material, and the thermal conductivity of common natural graphite materials is generally between 66 and 220 W / (m·K). A comparative experiment was conducted by adding graphite as an activated carbon material to the basic components to analyze the differences in thermal conductivity performance of the two materials at different ratios.
[0169] 1) Analysis of the influence of activated carbon on the thermal conductivity of materials
[0170] Fig.13The effect of different activated carbon additions on the thermal conductivity of the material. With the addition of activated carbon, the thermal conductivity of the material will improve. There will be a jump at the beginning. When 1% coal-based activated carbon is added, it can reach 2.48 W / (m·K). And with the increase of activated carbon addition, the thermal conductivity continues to increase, but the increase rate decreases. Among them, the thermal conductivity of the material with coal-based activated carbon is slightly higher than that of wood-based activated carbon. When the coal-based activated carbon addition is 5%, the thermal conductivity of the material is 2.67 W / (m·K).
[0171] 2) Analysis of the influence of graphite on the thermal conductivity of materials
[0172] like Fig.14 The figure shows the change of thermal conductivity of the material under different graphite additions. From the results, it can be seen that when 10% graphite is added, the thermal conductivity is 2.059 W / (m·K), which is nearly 21% higher than that before graphite is added. When the addition of graphite is 4% to 6%, the thermal conductivity increases significantly. At the same time, it can be seen that the growth rate decreases when graphite is just added and the addition is 6% to 10%, indicating that the addition of graphite can improve the heat transfer performance of the material, but the thermal conductivity is better when the addition is appropriate.
[0173] 3) Comprehensive analysis of the effects of the two materials on thermal conductivity
[0174] By comparison Fig.13 and 14 It can be found that when the basic ratio is the same, the thermal conductivity of the material with 5% coal-based activated carbon is increased by 22.9% compared with the material with 10% graphite, and the thermal conductivity of the material with 5% wood-based activated carbon is increased by 19.9% compared with the material with 10% graphite. When the amount of activated carbon added is less than that of graphite, the material with activated carbon still has excellent thermal conductivity. This is because activated carbon has good intermolecular forces, which can better condense the gravel and the cementitious material together during the solidification process of the material, so there are basically no pores on the surface of the material after solidification. Therefore, activated carbon can make the thermal conductivity of the material itself better by increasing the density of the material.
[0175] Continuing to increase the amount of activated carbon added can improve the thermal conductivity of the material, but the increase is small. Because the activated carbon has extremely strong adsorption, it will be adsorbed on the surface of gravel or combined with bentonite particles with good adsorption, thereby reducing the fluidity of the slurry. The slurry with activated carbon added is in a "creamy" state. Although the fluidity is not high, the slurry is very uniform and soft. This is because the activated carbon increases the homogeneity of the slurry. Regarding fluidity, since there is no clear national standard, according to engineering experience, when the amount of activated carbon added exceeds 5%, the impact on the fluidity of the material is not within an acceptable range.
[0176] (3) Experimental scheme of the effect of graphite and activated carbon on the adsorption performance of materials of the present invention:
[0177] Activated carbon is a porous material made by high-temperature carbonization of materials such as wood, coal, and fruit shells. Its pores can account for 70% to 80% of its total volume. The developed microporous structure gives this type of material a huge specific surface area, which also makes it have a strong adsorption capacity. 2 The six-membered ring structure produced after hybridization does not have adsorption properties.
[0178] The adsorption experiment of the present invention uses a combination of five materials to test the adsorption performance of the organic pollutant methylene blue and the inorganic pollutant hexavalent chromium. The cement + quartz sand + 5% bentonite material with a water-cement ratio of 0.95 and a sand-cement ratio of 2 is used as a blank control group, and then 3% and 5% of wood and coal-based activated carbon are added to this material, respectively, to determine the adsorption relationship between the addition amount of the five materials and the methylene blue solution and the hexavalent chromium solution, and the adsorption constant KL is used as a measurement standard to study the adsorption performance of the materials under different components.
[0179] 1) Analysis of adsorption performance of organic pollutants
[0180] Methylene blue is a common chemical indicator widely used in various industries such as industrial dyes, biomedicine and aquaculture. Methylene blue is also one of the main pollutants in industrial wastewater, and is toxic and difficult to degrade. The present invention selects a methylene blue solution to test the adsorption performance of the comprehensive environmentally friendly backfill material on organic pollutants.
[0181] (a) Methylene blue solution standard line
[0182] Before the experiment begins, you need to make a methylene blue solution mark ( Fig.15 ), which is used to determine the relationship between solution concentration and absorbance, and is used as a reference for the concentration corresponding to the absorbance in subsequent experiments. Pure water and methylene blue solutions with concentrations of 2 mg / L, 4 mg / L, 5 mg / L, 6 mg / L, 8 mg / L and 10 mg / L were selected, and the absorbance (Abs) of the solutions at different concentrations was measured using a spectrophotometer. Then, a linear fit was performed on the test results, and the standard equation with a goodness of fit of 0.9923 was obtained:
[0183] (1)
[0184] Where: A—absorbance of methylene blue, (au);
[0185] C—Methylene blue concentration, (mg / L).
[0186] (b) Experiment on the influence of material dosage
[0187] The adsorption capacity, adsorption strength and adsorption mechanism of the material for pollutants can be determined according to the parameters of the adsorption equation. Common adsorption equations include the Langmuir isotherm adsorption model:
[0188] (2)
[0189] Where: Ce—equilibrium concentration (mg / L);
[0190] Qe—equilibrium adsorption (mg / g);
[0191] Qm—monolayer saturated adsorption capacity (mg / g);
[0192] KL—Langmuir adsorption constant (L / mg), which indicates the affinity of the adsorbent for the adsorbate in the solution.
[0193] Depend on Fig.16 , 17 It can be seen that when the initial concentration of methylene blue solution is 10 mg / L, the addition of activated carbon at 0.08g has a relatively ideal removal rate, and its change trend is that before the ideal dosage, the dosage and removal rate are positively correlated. According to the results, the adsorption effect is significantly improved after adding a small amount of activated carbon.
[0194] (c) Adsorption isotherm
[0195] As shown in Table 1, compared with the combination of cement and sand, the maximum adsorption capacity after adding bentonite is significantly improved, and the increase in the Langmuir adsorption constant KL also shows that the adsorption process of methylene blue by cement-based materials modified with activated carbon is easier to proceed. Comparing the adsorption performance of the materials after adding the two activated carbons, the adsorption effect of coal-based activated carbon is better than that of wood-based activated carbon.
[0196] By comparing KL, it can be found that the material with added wood activated carbon has a lower affinity for methylene blue adsorption than the material with only added bentonite. This is because cement-based materials are alkaline during the hydration process, while wood activated carbon is acidic. Although the maximum adsorption capacity is increased after the precipitation is formed, the affinity with methylene blue is reduced. Comprehensively analyzing the six materials, it can be found that the material with 5% coal-based activated carbon and bentonite added to cement has the highest maximum adsorption capacity Qm, which is more than 4 times higher than that of pure cement mortar and about 67.9% higher than that of only adding bentonite. At the same time, the substantial increase in KL also shows that the addition of activated carbon makes the adsorption process easier, which is beneficial to improving the adsorption capacity of the material.
[0197] 2) Inorganic pollutant adsorption performance test
[0198] Chromium (Cr) is widely used in the chemical industry. Cr (VI) can cause serious harm to human health and can enter groundwater and crops through soil pores. The present invention selects hexavalent chromium solution to test the adsorption performance of comprehensive environmentally friendly backfill materials on inorganic pollutants.
[0199] (a) Hexavalent chromium solution standard line
[0200] Before the experiment begins, it is necessary to mark the hexavalent chromium solution ( Fig.18 ) Select pure water and hexavalent chromium solutions with concentrations of 0.02 mg / L, 0.04 mg / L, 0.08 mg / L, 0.12 mg / L, 0.16 mg / L, 0.2 mg / L, 0.4 mg / L, 0.6 mg / L, 0.8 mg / L and 1.0 mg / L, use a spectrophotometer to measure the absorbance (Abs) of the solutions at different concentrations, and then perform linear fitting on the test results to obtain the hexavalent chromium absorption standard curve equation with a correlation R2=0.9931:
[0201] y=0.7361x-0.0048 (3)
[0202] Where: y—measured absorbance, (au);
[0203] x—concentration of hexavalent chromium solution, (mg / L).
[0204] (b) Experiment on the influence of material dosage
[0205] Fig.19 —22, it can be found that with the increase of the amount of backfill material added, the adsorption amount and removal rate both increase significantly. The slope of the adsorption amount is steeper and changes faster in the range of 0.32-0.64 g. When the amount is 0.80 g, the rate of increase of the adsorption amount slows down but still increases. From the values of the two, it can be seen that the addition of coal-based activated carbon backfill material has a significant effect on the removal of Cr. 6+ The adsorption amount and adsorption rate of the cement-based materials were significantly larger than those of the other groups, indicating that the cement-based materials with added coal-made activated carbon had better adsorption effect on heavy metal Cr than the cement-based materials with added wood-made activated carbon and the control materials.
[0206] According to the above experimental results, considering the effects of different addition amounts of various materials on fluidity, thermal conductivity and adsorption performance, the comprehensive environmentally friendly backfill materials mixed with 3% and 5% coal-based activated carbon are the best choices.
[0207]
[0208]
[0209] The above are only several implementation modes of the present invention. The protection scope of the present invention is not limited to the above embodiments. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications made without departing from the concept of the present invention are all within the protection scope of the present invention.
Claims
1. A comprehensive environmentally friendly ground source heat pump backfill material, characterized by: It is composed of basic components and admixtures, wherein the basic components are composed of silicate cement, quartz sand, water and bentonite, and the admixture is powdered activated carbon; The weight ratio of Portland cement, quartz sand, water, bentonite and powdered activated carbon is: Portland cement: 1.0 part; Quartz sand: 2.0 parts; Water: 0.95 parts; Bentonite: 0.16 parts; Powdered activated carbon 0.03-0.05 parts; The powdered activated carbon is powdered wood activated carbon or powdered coal activated carbon; The powdered wood activated carbon has a pH value of 2.6, a particle size of 200 mesh, and a specific surface area of 1056 m 2 / g, iodine value is 1077mg / g, moisture is 4.9%; the pH value of the powdered coal-based activated carbon is 7.6, the particle size is 200 mesh, and the specific surface area is 1089 m 2 / g, iodine value is 1075 mg / g, water content is 5.5%; The preparation method comprises the following steps: S1: preparing the raw materials of each component according to the weight ratio; cleaning the mixing pot of the cement mortar mixer and drying the mixing pot; S2: Add the other raw materials except water into a stirring pot, stir and mix well to obtain a dry material mixture; S3: Add water to the dry material mixture and stir until the slurry is uniform to obtain the comprehensive environmentally friendly ground source heat pump backfill material.
2. The comprehensive environmentally friendly ground source heat pump backfill material according to claim 1 is characterized by: The weight ratio of Portland cement, quartz sand, water, bentonite and powdered activated carbon is: Portland cement: 1.0 part; Quartz sand: 2.0 parts; Water: 0.95 parts; Bentonite: 0.16 parts; 0.05 parts of powdered activated carbon.
3. The comprehensive environmentally friendly ground source heat pump backfill material according to claim 1 is characterized by: The strength grade of the silicate cement is ≥42.
5.
4. The comprehensive environmentally friendly ground source heat pump backfill material according to claim 1 is characterized by: The particle size of the quartz sand is 40-70 mesh, and the bulk density is 1.87 g / cm 3 .
5. The comprehensive environmentally friendly ground source heat pump backfill material according to claim 1 is characterized by: The bentonite is sodium bentonite with a particle size of 200 mesh and a bulk density of 1.6 g / cm 3 .
6. The comprehensive environmentally friendly ground source heat pump backfill material according to claim 1 is characterized by: In step S2, the cement mortar mixer is set to run at a low speed, that is, rotation at 140±5r / min, revolution at 62±5r / min, and mixing time at 120s; In step S3, the water is divided into two equal parts, one equal part of water is first added to the dry material mixture, and the cement mortar mixer continues to run at a low speed for 240 seconds; then the cement mortar mixer is stopped, and the material on the inner wall of the mixing pot is scraped into the mixing pot with a scraper; another equal part of water is added, and the cement mortar mixer is set to run at a high speed, that is, rotation at 285±10r / min, revolution at 125±10r / min, and the mixing time is 180s.